Pengembangan Budaya Literasi Sekolah sebagai Upaya Meningkatkan Keterampilan Membaca dan Menulis Siswa dalam Pembelajaran Bahasa Indonesia di SMP - Pratama, Gerry; Wasliman, Eva Dianawati; Handayani, Sri (Educatoria : Jurnal Ilmiah Ilmu Pendidikan, 2026)
This study aims to analyze the implementation of school literacy culture and its impact on improving students' reading and writing skills in Indonesian learning at the junior high school level. The research uses a descriptive qualitative approach. Data was collected through learning observations, interviews with school principals, Indonesian teachers, and students, and document analysis. The results of the study show that the implementation of literacy programs that are managed in a planned and systematic manner, such as fifteen-minute reading activities, the development of literacy corners in various school locations, library optimization, and writing guidance, are able to improve students' reading and writing skills. Improvements can be seen in the ability to understand texts, find main ideas, analyze the structure and language of the text, and arrange writing sequentially and logically. The success of the literacy program is influenced by the strong leadership of the principal as a policy maker, motivator, supervisor, and initiator of cooperation, the pedagogical commitment of teachers, the availability of adequate facilities, and the active participation of parents and the school community. Supporting factors include the commitment of the principal and teachers, the support of parents and school committees, a conducive school environment, and adequate facilities. Inhibiting factors include challenges in the consistency of program implementation, limited book collections, differences in student motivation, limited time and budget, and competition with gadgets. This research emphasizes the importance of strengthening school literacy culture as part of education management to improve the quality of Indonesian learning in junior high schools.